Dynamic Contrast-Enhanced Computed Tomography: A New Diagnostic Tool to Assess Renal Perfusion After Ischemia-Reperfusion Injury in Mice. Issue 5 (May 2016) - Braunagel, Margarita; Helck, Andreas; Wagner, Anne; Schupp, Nina; Bröcker, Verena; Reiser, Maximilian; Notohamiprodjo, Mike; Meiser, Bruno; Habicht, Antje
Abstract : Objective: The aim of this study was to investigate the value of dynamic contrast-enhanced computed tomography (CT) in the assessment of renal perfusion parameters after ischemia-reperfusion (I/R) injury in an experimental murine model. Materials and Methods: Balb/cJ wildtype mice were subjected to 45 minutes (AKI45 ) or 60 minutes (AKI60 ) of unilateral warm I/R injury by clamping the pedicle of the right kidney. Two, 7, and 18 days after right I/R injury, renal blood flow (RBF), renal volume of distribution (RVD), and mean transit time were quantitatively assessed in the cortex of both kidneys by dynamic contrast-enhanced CT. Acute tubular injury (ATI) was assessed by histologic analysis using a semiquantitative sum score (score, 0–18) and correlated with RBF, RVD, and mean transit time. Results: Histologic signs of ATI could be detected in the clamped kidneys in both groups already at day 2. Pathologic features of ATI worsened in AKI60 until day 18 (score, 7 ± 0), whereas mice in AKI45 group showed amelioration over time (score, 4 ± 2). Renal blood flow was significantly reduced in ischemic kidneys in AKI45 (287 ± 32 mL/100 mL per minute; P < 0.01) and AKI60 group (249 ± 73 mL/100 mL per minute; P < 0.01) as compared with that in healthy kidneys (402 ± 49 mL/100 mL per minute) on day 2. It decreased further at day 7 in both groups (AKI45 : 165 ± 44 mL/100 mL per minute, P < 0.01; AKI60 : 151 ± 72 mL/100 mL per minute, P < 0.05) and improved at day 18 in AKI45 (261 ± 11 mL/100 mL per minute, P < 0.05) and to a lesser degree in AKI60 (197 ± 52 mL/100 mL per minute, P > 0.05). Values of RVD paralleled RBF at all time points. Renal blood flow ( r = −0.79; P < 0.01) and RVD ( r = −0.8; P < 0.01) significantly correlated with the histological damage score (Spearman rank correlation). Conclusions: Dynamic contrast-enhanced CT is a noninvasive method to determine renal perfusion changes in acute kidney injury. It might be a valuable diagnostic tool to predict outcome or monitor treatment effects of renal I/R injury.